Automated seed sowing machine for uneven surface - Md Fauadi, Muhammad Hafidz Fazli; Muhammad Nanda, Muhammad Narvin; H. Rahman (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Seed sowingis a crucial agricultural step as it marks the beginning of the plant's life cycle and establishes the foundation for healthy growth and successful cultivation. Traditional manual seeding process methods struggle with uneven surfaces, leading to inefficient seed distribution and reduced crop yields. The solution is by integrating sensors, actuators, and intelligent control systems to address these challenges. This study proposesan automated seed sowing machine designed specifically for uneven surfaces. The mechanism employs the combination of mechanical design and automation using microcontroller to assess real-time conditions. A central control unit processes this data to adjust seeding depth, spacing, and rate dynamically. It features a precision seeding unit with electric actuators for accurate seed placement, along with a robust chassis and adaptive systems to navigate rough surfaces. Based on the experiment conducted, it is concluded that the machine is capable to execute the seed sowing task properly.